PENGARUH PEMBIAYAAN, PELATIHAN KEWIRAUSAHAAN, DAN EFIKASI DIRI TERHADAP INTENSI BERWIRAUSAHA POSDAYA BERKAH V KALINYAMAT WETAN KOTA TEGAL - maulida dwi kartikasari; sumarno sumarno (Universitas Lancang Kuning, 2017)
training and entrepreneurial self-efficacy to the intention Posdaya Berkah V KalinyamatWetan Tegal. This research as a form of training for members Posdaya Berkah V KalinyamatWetan. Methods of data collection was conducted using a survey of 40 members of PosdayaBerkah V determined randomly. Data collected include financing instruments,entrepreneurship training, and self-efficacy. Data were collected through interviews using aquestionnaire (questionnaire) were prepared.The results showed that the significant effect onthe financing of entrepreneurial intentions. This is consistent with the hypothesis 1. However,entrepreneurial training and self-efficacy does not significantly influence entrepreneurialintentions.Keywords: Financing, training, entrepreneurship intention